2008
DOI: 10.1007/s10528-008-9184-4
|View full text |Cite
|
Sign up to set email alerts
|

A Novel RUNX2 Mutation in Cleidocranial Dysplasia Patients

Abstract: Cleidocranial dysplasia (CCD) is an autosomal-dominant heritable skeletal disease caused by heterozygous mutations in the RUNX2 gene. Here, the RUNX2 gene was analyzed within a CCD family from China, and a novel missense mutation (c. 475G --> C [p.G159R]) was identified. Normal and mutant RUNX2 expression vectors were then constructed and expressed transiently in NIH3T3 cells. Immunofluorescent staining and Western blotting showed that wild-type RUNX2 protein was localized exclusively in the nucleus; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…B: The schematic shows functional domains and the mutation sites of RUNX2 in CCD patients. Mutations reported in previous studies [Otto et al, 2002; Yoshida et al, 2002; Tessa et al, 2003; Kim et al, 2006; Pal et al, 2007; Xuan et al, 2008; Li et al, 2009; Zhang et al, 2009; Cardoso et al, 2010; Gao et al, 2010; Wang et al, 2010] are indicated below the structure of RUNX2 protein (the 521 amino acids isoform starting with MASNS). The new mutation E366X identified in the present study is indicated above the structure.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…B: The schematic shows functional domains and the mutation sites of RUNX2 in CCD patients. Mutations reported in previous studies [Otto et al, 2002; Yoshida et al, 2002; Tessa et al, 2003; Kim et al, 2006; Pal et al, 2007; Xuan et al, 2008; Li et al, 2009; Zhang et al, 2009; Cardoso et al, 2010; Gao et al, 2010; Wang et al, 2010] are indicated below the structure of RUNX2 protein (the 521 amino acids isoform starting with MASNS). The new mutation E366X identified in the present study is indicated above the structure.…”
Section: Resultsmentioning
confidence: 96%
“…DNA was extracted from blood samples with the QIAamp Blood Kit (Qiagen). Exons 0–7 of the RUNX2 gene were amplified from genomic DNA and sequenced as previously outlined [Xuan et al, 2008]. Briefly, the PCR reaction was performed with a 5 min denaturation at 94°C, followed by 25 cycles, each with denaturation at 94°C for 30 s, primer annealing for 30 s at different temperature respectively (Table I), and product extension at 72°C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…The type and location of specific mutations within the RUNX2 gene impact the expressivity of the CCD phenotypic findings, thus correlating the genetic variations in the corresponding gene with the clinical manifestations of the syndrome [9]. …”
Section: Introductionmentioning
confidence: 99%
“…(12) Abnormalities in RUNX2 function can lead to cleidocranial dysplasia (CCD), in which there is defective ossification of the cranial bones with large fontanels and delayed closing of the sutures with complete or partial absence of the clavicles. (13)(14)(15)(16)(17)(18)(19) Mice with homozygous mutations in RUNX2 cannot survive after birth owing to breathing defects caused by the absence of ossification of the ribs. (20,21) The functions of RUNX2 and SOX9 are controlled by transcriptional and posttranscriptional regulation, including ubiquitination, phosphorylation, and acetylation.…”
Section: Introductionmentioning
confidence: 99%